Rock structure estimation using smoothness-constraint least-squares inversion data geolistric resistivity of schlumberger configuration in Bukit Lantiak Padang Selatan - Rahmi Kurnia Putri (Department of Physics – Universitas Negeri Padang UNP, 2014)
A research about rocks structure has been done in Bukit Lantiak Padang Selatan. The aim of this research are determine kinds of rocks, rocks structure and model 3D spread of rocks in landslide area, Bukit Lantiak. This research use a Resistivity Geoelectrical method with Schlumberger Configuration. Data were collected by ARES Multielectrode in 4 lines. The data were interpreted by Least-Squares inversion to obtain a 2D model and 3D model of earth’s surface that consists of depth and resistivity value. The result of this research showed that the kinds of rocks in this area consist of Andesite, Clay, Sandstone and Limestone. Generally rock structure in this area consists of Sandstone at depth 6 m from surface , next layer consists of Limestone at depth more than 5,3 m, Clay was found at depth 34, 4 m until 43,4 m and the last layer was found Andesite. Model 3D showed that Sandstone and Clay found in all area, Limestone found in Southwestern, Andesite found in northeaster of research location